A guide to utilizing implementation science for genetic counseling. - Kulchak Rahm, Alanna; Cragun, Deborah (Journal of Genetic Counseling, 2025)
Implementation Science (IS) is a growing field that provides tools to understand and facilitate the uptake of research and policies into healthcare delivery to improve quality and outcomes. Genetic counselors are uniquely positioned as the implementers of genomic medicine, with many seeking to learn about and incorporate IS into genetic counseling education and practice. We propose that genetic counselors can utilize IS in many areas of their practice and research, such as when applying new evidence or integrating guidelines into practice and when leading or assisting with quality improvement or research projects. Our goal with this paper is to provide a general overview of IS and to introduce the basics of theories, models, and frameworks, study designs and methods, and measuring IS outcomes. In addition, we briefly discuss IS tools useful for understanding and eliminating disparities and inequities, and how IS can assist genetic counselors with policy or clinical guideline implementation. It is our belief that incorporating IS tools into practice and teaching IS approaches will add to the value of genetic counselors. To that end, our hope is that this paper becomes a starting point for the integration of IS into the profession to improve the impact of our services in every context, demonstrate the value we add in the practice of genomic medicine, and contribute to the growth and evolution of our profession.